Selection for divergent body size alters rates of embryonic skeletal muscle formation and muscle gene expression patterns. (10th December 2015) - Lu, Yue; Bradley, Jennifer S.; Siegel, Paul B.; Yang, Ning; Johnson, Sally E.
Abstract : The impact of divergent selection for body size on embryogenesis is poorly understood. The objective of this experiment was to document skeletal muscle development during embryogenesis in two lines of chickens that display divergent growth as adults. Results reveal that after 54 generations of opposing selection from a common founder population, the embryos from the low weight select (LWS) line develop more rapidly during early embryogenesis than those from the high weight select (HWS) line. Muscle formation during the late embryonic period is more rapid and extensive in the HWS embryo than in the LWS contemporary. Isolated muscle progenitors from embryonic day 10 HWS embryos proliferated more rapidly, forming fibers sooner with a larger size than the LWS cells. The limited myogenic capacity of the LWS progenitor cells is not attributed to altered patterns of expression of Pax7, Pax3 or the myogenic regulatory factor genes. Members of the fibroblast growth factor family are potent mitogens and inhibitors of myoblast differentiation. Transcript abundance of FGF2 and FGF4 was measured in cultures of HWS and LWS progenitors as a function of time. The pattern of expression of FGF4 was similar between HWS and LWS with a large increase between days 1 and 3 followed by a reduction at day 5 of culture. Expression of FGF2 in LWS muscle cells did not change while a significant reduction in FGF2 expression was observed by day 5 in the HWS. Our results indicate that divergent selection for postnatal growth has altered embryonic development. Abstract : Results presented, herein, demonstrate that divergent selection for postnatal growth has altered embryonic development. Protracted muscle formation in chick embryos may be due to sustained expression of FGF2.